EFEKTIVITAS SIRIP PEREDAM DALAM MEREDAM EFEK FREE SURFACE YANG MEMPENGARUHI GERAKAN ROLLING KAPAL MODEL - Dwi Putra Yuwandana; Yopi Novita; Budhi Hascaryo Iskandar (Fakultas Perikanan dan Ilmu Kelautan, 2015)
Ships carrying liquid cargo will experience free surface effects. It is a free movement of liquid cargo in the hold, especially during rolling motions. The use of absorber fins in hold is an alternative to reduce the free surface effect. This study aimed to determine the minimum size of absorber fins that were still effective to reduce the effect of free surface affecting the rolling motion of ship. The experimental method was applied by using a model ship with hold. Four size of absorber fins were used as treatments in this experiment. Data were analyzed by comparative numerical and statistical tests using a completely randomized design. During the experimental, four variable that were observed such as angle of rolling ship model, rolling duration, rolling frequency and rolling period. The result showed that the use of absorber fins with the size of (10%) of the free surface area was effective to reduce the free surface effect toward the rolling motion of ship models.